Small Molecules Make a Big Difference: A Solvent‐Controlled Strategy for Building Robust Conductive Network Structures in High‐Capacity Electrode Composites. Issue 8 (26th April 2018) - Fu, Xuewei; Wang, Yu; Tuba, James; Scudiero, Louis; Zhong, Wei‐Hong
Abstract: Building robust conductive network with polysulfides adsorption function in sulfur cathode composites is critical for lithium‐sulfur (Li‐S) batteries. Here, a very viable approach to realize this goal is reported. Only with the aid of a co‐solvent (acetic acid) of water, an advanced conductive network is established in the sulfur cathode without any additional treatment on the pristine materials. It is found that acetic acid surprisingly acts as an advanced co‐solvent and dispersant that can tune the chain structures of the binders and the surface properties of conductive agent and sulfur particles. Consequently, it notably strengthens the interactions among all the components, and helps build a functional and robust conductive network. The mechanical properties studied via rheological method and the electrochemical performance of the sulfur composites all are significantly enhanced compared with the counterpart using water as the solvent that has been traditionally viewed as a good solvent for preparing sulfur cathode with aqueous binders. This study reveals that the mixture of acetic acid and water is an effective solvent system for preparing high‐performance sulfur cathodes, and demonstrates that the rheological method is an important tool for characterizing mechanical properties of the electrode composites. Abstract : A solvent‐controlled strategy is presented to control the microstructures and interfaces in sulfur cathode. The mechanical properties of the electrode composites are studied using rheological testing. The reported strategy for controlling the structures/interfaces and the new method for characterizing mechanical properties are in critical need for the design of advanced electrode composites.